Study of an autoresonance method of accelerating particles by electromagnetic waves; Soviet Atomic Energy; Vol. 22, № 1 - Vorobyev А. А. Alexander Akimovich; Didenko A. N.; Ishkov A. P.; Kolomenskii A. A.; Lebedev A. N.; Yushkov Y. G. Yuri Georgievich (1967, 1967)
Aspects of the autoresonanee acceleration of particles by fast waves in smooth wave-guides are considered. The results are confirmed by experiments carried out in the 10-cm waveband. The maximum energy of electrons so accelerated was about 700 keV